Best Proximity Coincidence Point Results for α, D-Proximal Generalized Geraghty Mappings in JS-Metric Spaces. (23rd November 2020) - Wiriyapongsanon, Atit; Charoensawan, Phakdi; Chaobankoh, Tanadon
Abstract : We introduce a type of Geraghty contractions in a J S -metric space X, called α, D -proximal generalized Geraghty mappings. By using the triangular-α, D -proximal admissible property, we obtain the existence and uniqueness theorem of best proximity coincidence points for these mappings together with some corollaries and illustrative examples. As an application, we give a best proximity coincidence point result in X endowed with a binary relation.